Qatar Tourists to Indonesia in Boston Consulting Group (BCG), PESTLE, and Porter’s Five Forces - Ramiz Haq (Universitas Muhammadiyah Jember, 2025)
Foreign travellers have an important part in deciding the progress of a tourist site. Understanding international tourist expenditure is critical due to fast changes in segmentation. Despite its tiny size, Qatar is a country rich in oil and gas making it one of the wealthiest in terms of GDP per capita, with 72,760 USD, dominated by the industrial sector (50.3%) and services (49.5%). Thus, Qatari citizens provide a prospective market for inbound tourists to Indonesia. This research employs Boston Consultant Group (BCG) methodology as a foundation to examine Qatari tourist expenditure in Indonesia based on spending segmentation. In the follow-up, BCG outcomes are described using PESTLE theory and Porter Five Forces theory. It is intended that findings of this analysis would serve as a marketing strategy for Indonesian tourism products to Qatar in next years.